Smoking among adolescents and associated factors in rural areas - Mohd Mokhtar, Hanida Hani; Abdul Ghani, Nurul Farhana; Jaafar, Siti Nur Illiani; Ahmad, Aini; Arofiati, Fitri (Faculty of Nursing, Universitas Indonesia, 2023)
Smoking among adolescents is a major health-related issue in Malaysia. However, information concerning recent smoking rates and how they correlate among adolescents in rural areas is still limited. This study aimed to determine the percentage of adolescent smokers among high school students, examine their level of nicotine dependence, and study the association between sociodemographic data and smoking status. A cross-sectional study was conducted at one of the high schools located in the rural area of Bandar Tun Abdul Razak, Pahang, Malaysia. A convenience sampling method was used to select the participants, as only Form 2 students were available during the data collection. In total, 113 respondents were recruited for the study. The data, collected using self-administered questionnaires, were analyzed using chi-square analysis and Fisher’s exact test analysis. The results showed that the prevalence of adolescent smokers among high school students was quite high (25.7%). Among the adolescent smokers, 65.5% had low nicotine dependence, and 34.5% had moderate nicotine dependence. Moreover, 21.4% of them admitted that they had tried other substances or drugs in addition to cigarettes. Peer pressure was the major factor in smoking (69.0%), followed by curiosity (27.6%), the smoking family members' influence, stress or tension, and others (3.4% each). The only significant association (p < 0.001) was between gender and smoking status. These findings showed that the proportion of smokers among adolescents has been increasing over the years; thus, effective strategies, such as peer advocacy of smoking cessation, may be needed among this population.